The Urgency Of Teacher Competence In Understanding The Psychological Characteristics Of Students In Full-Day School System - Suci Hidayati; Yuliana Nur Mustagfiroh; Sumrotul Ilmiyah (AL-WIJDÃN Journal of Islamic Education Studies, 2023)
Differentiated learning based on student characteristics is one of the keys to success in learning, especially in schools with a Full Day School system. Learning is effective when the teacher can choose and determine an approach based on an analysis of the characteristics of the students because the study hours in Full Day School systems are longer than in general schools. The research subjects were MTs students. Ahmad Yani Jabung class 9 whose study hours use the Full Day School system. This study describes the importance of teacher pedagogical competence, especially aspects of understanding the psychological characteristics of students, including; (1) Teacher competence in recognizing the psychological characteristics of students in the class. (2) Teacher competence in choosing approaches and methods based on students' psychological characteristics. If the two competencies of teachers who teach at schools with the Full Day School system are not optimal, there will be an impact on changes in the psychological characteristics of students while studying in class. The results of this study used descriptive qualitative research with the variable Student Psychological Characteristics. The results of the study show that (1) there are still more teachers who do not understand the psychological characteristics of students, (2) there are 50% of students cannot take the learning process seriously, and (3) psychologically the impacts that occur on students such as boredom, fatigue and weak in capturing lessons.  Keywords: Full Day School, Psychology Characteristics